‘Knowing as we go’: a Hunter-Gatherer Behavioural Model to Guide Innovation in Sport Science - Woods, Carl T. (Sports Med Open, 2020)
Where do novel and innovative ideas in sport science come from? How do researchers and practitioners collectively explore the dynamic landscape of inquiry, problem, solution and application? How do they learn to skilfully navigate from current place and practice toward the next idea located beyond their current vantage point? These questions are not just of philosophical value but are important for understanding how to provide high-quality support for athletes and sport participants at all levels of expertise and performance. Grounded in concepts from social anthropology, and theoretically positioned within an ecological dynamics framework, this opinion piece introduces a hunter-gatherer model of human behaviour based on wayfinding, situating it as a conceptual guide for implementing innovations in sport science. Here, we contend that the embedded knowledge of a landscape that guides a successful hunting and gathering party is germane to the pragmatic abduction needed to promote innovation in sport performance, leading to the inquisition of new questions and ways of resolving performance-preparation challenges. More specifically, exemplified through its transdisciplinarity, we propose that to hunt ‘new ideas’ and gather translatable knowledge, sport science researchers and practitioners need to wayfind through uncharted regions located in new performance landscapes. It is through this process of navigation where individuals will deepen, enrich and grow current knowledge, ‘taking home’ new ideas as they find their way.